1994
DOI: 10.1007/bf02521342
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for psychiatric inpatient assaults on staff

Abstract: The risk of psychiatric patient assaults on staff members is increasing yearly, with resultant increases in employee victim suffering, medical expense, and lost productivity. Traditionally considered a clinician responsibility, the management of patient violence also has important administrative implications. This article presents a review of the risk factors associated with violence that includes the characteristics of patients who assault but adds the characteristics of employee victims of such assaults as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
61
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(70 citation statements)
references
References 41 publications
9
61
0
Order By: Relevance
“…Younger age may be a reflection of lack of work experience and lower education, resulting in a nurse's inability to handle potentially difficult situations. Previous reports have shown that personal risk factors for workplace violence included gender, education, childhood abuse or previous assault experience 4,7,8,18,[21][22][23][24] . We did not find gender to be a significant determinant, probably due to the predominance of females in the nursing profession in Thailand.…”
Section: Discussionmentioning
confidence: 99%
“…Younger age may be a reflection of lack of work experience and lower education, resulting in a nurse's inability to handle potentially difficult situations. Previous reports have shown that personal risk factors for workplace violence included gender, education, childhood abuse or previous assault experience 4,7,8,18,[21][22][23][24] . We did not find gender to be a significant determinant, probably due to the predominance of females in the nursing profession in Thailand.…”
Section: Discussionmentioning
confidence: 99%
“…There have been several reviews of the characteristics of psychiatric patient assailants (5)(6)(7)(8)(9)(10)(11). These studies have noted two types of patients at high risk for assaulting staff.…”
mentioning
confidence: 99%
“…Similar definitional and methodological difficulties have been encountered by researchers studying the patient factors common to workplace violence (Flannery et al 1994).…”
Section: Staff Factorsmentioning
confidence: 80%
“…In an extensive review of risk factors associated with violent behaviour in psychiatric inpatients, Flannery, Hanson and Penk (1994) examined the impact of patient and staff characteristics and a range of contextual variables on frequency of violent events. Notably, the authors discussed the difficulties associated with identifying the patient characteristic due to the varying definitions and underreporting.…”
Section: Client Variablesmentioning
confidence: 99%
See 1 more Smart Citation